Teori - Teori Kebenaran sebagai Fondasi Etika Keilmuan - Hapsari, Cecilia Indah; Agung Winarno; Subagyo Subagyo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The background of this research stems from the need to reexamine the position of theories of truth in the philosophy of science as a basis for the formation of scientific ethics amid the increasingly complex development of modern science. The concept of truth not only functions as an epistemological guideline in determining the validity of knowledge, but also has a normative dimension that influences the integrity, honesty, and responsibility of scientists in the research process. Based on this, this study aims to analyze various theories of truth, including correspondence, coherence, pragmatism, consensus, performativity, deflationism, and foundationalism, and to explain the relevance of each approach to the formation of scientific ethics. This study uses a literature review method with a descriptive-analytical approach through a systematic search of relevant journals, books, and academic sources, which are then analyzed through thematic synthesis to obtain a comprehensive conceptual understanding. The findings show that each theory of truth has a unique contribution to building scientific ethics. Correspondence emphasizes the importance of empirical verification, coherence emphasizes rational consistency, pragmatism highlights theoretical functionality, consensus places scientific dialogue as the legitimization of knowledge, performativity connects truth with action, the deflationary approach emphasizes clarity of language, and foundationalism provides a stable epistemic foundation. The implications of this research show that the integration of these various theories can form a more robust, holistic, and adaptive framework of scientific ethics to the demands of modern scientific practice. This framework is expected to strengthen an honest, transparent, and accountable scientific culture, while opening opportunities for the development of epistemology-based research ethics guidelines in the future.